DAMPAK DUKUNGAN ORGANISASI DAN KREATIVITAS KARYAWAN TERHADAP PERILAKU KERJA INOVATIF MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) SEBAGAI VARIABEL MEDIASI - Mei Ie; Henny Henny; Emma Cecilia; Aileen Kristanti (PROSIDING SERINA, 2021)
Innovative work behavior is one that helps individuals become more creative and have a positive impact on performance and organization while organizational support is the belief of employees to know the extent to which their organization supports employees in aspects of their work. Creativity is all the ability related to form something new and creative. Organizational Citizenship Behaviour (OCB) is the behavior of a person who acts outside his obligations to help his fellow colleagues. The goal of this study was to determine the impact of organizational support and employee creativity on innovative work behavior through Organizational Citizenship Behaviour (OCB) as a mediation variable. Sampling methods use non-probability sampling techniques with purposive sampling techniques.  The results of this study showed that organizational support negatively but not significantly affects employees' innovative work behaviors, employee creativity negatively affects but does not significantly affect employees' innovative work behaviors,  Organizational Citizenship Behavior  (OCB) has a significant and positive influence on innovative work behavior in employees, organizational support affects negatively but insignificantly.  In the context of innovative work behavior with mediated Organizational Citizenship Behaviour (OCB), employee creativity has a significant and positive influence on innovative work behavior by mediating Organizational Citizenship Behaviour (OCB) on employees. The implication of this research for the company is expected to benefit field workers at PT XYZ, and solve various problems related to innovative work behavior.